Myth and Authority : Giambattista Vico's Early Modern Critique of Aristocratic Sovereignty. - Bertland, Alexander U. (State University of New York Press, 2022)
Argues that Giambattista Vico's early modern account of Roman mythology was a sophisticated attempt to present an epistemological and political critique of the aristocratic way of conceiving the world.
Description based upon print version of record.
Keywords: Vico, Giambattista, -- 1668-1744; Political science -- Philosophy.; Despotism -- Philosophy.; Despotisme -- Philosophie.